2022
DOI: 10.1111/rda.14204
|View full text |Cite
|
Sign up to set email alerts
|

Tribulus terrestris can suppress the adverse effect of toluene on bovine and equine ovarian granulosa cells

Abstract: Influence of oil-related product toluene and herbal remedy puncturevine Tribulus terrestris L. (TT) on female reproduction is known. Yet, mechanisms of their action on ovaries in different species and potential protective effect of TT against adverse toluene action remain to be established. We studied the effect of toluene, TT, and their combination on ovarian granulosa cells from two mammalian species (cows and horses). Viability, markers of proliferation (PCNA) and apoptosis (bax), steroid hormones, IGF-I, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The plant Tribulus terrestris L. (TT) can be found in many regions of Asia and Africa and has been used in traditional Chinese medicine and Ayurvedic medicine as an herb to treat liver diseases for thousands of years. Tiliroside ( TS ), one of the main extractions from this herb ( 54 , 55 ), has been found to possess anti-inflammatory, anticholinesterase, and antioxidant activities ( 56 ). Moreover, our recent study has further revealed its multiple anticancer effects on HCC cells and, more importantly, its property of CAXIIi ( 32 ).…”
Section: Potential Carbonic Anhydrase XII Inhibitorsmentioning
confidence: 99%
“…The plant Tribulus terrestris L. (TT) can be found in many regions of Asia and Africa and has been used in traditional Chinese medicine and Ayurvedic medicine as an herb to treat liver diseases for thousands of years. Tiliroside ( TS ), one of the main extractions from this herb ( 54 , 55 ), has been found to possess anti-inflammatory, anticholinesterase, and antioxidant activities ( 56 ). Moreover, our recent study has further revealed its multiple anticancer effects on HCC cells and, more importantly, its property of CAXIIi ( 32 ).…”
Section: Potential Carbonic Anhydrase XII Inhibitorsmentioning
confidence: 99%